Improving reading fluency and comprehension in adult ESL learners using bottom-up and top-down vocabulary training - Oliver, Rhonda; Young, S. (2016)
The current research examines the effect of two methods of vocabulary training on reading fluency and comprehension of adult English as second language (ESL) tertiary-bound students. The methods used were isolated vocabulary training (bottom-up reading) and vocabulary training in context (topdown reading). The current exploratory and quasi-experimental study examines the effectiveness of these methods in two intact classes using preand posttest measures of students’ reading fluency and comprehension. The results show that bottom-up training had a negative impact on fluency and comprehension. In contrast, top-down training positively affected fluency but had no impact on comprehension. Further, the results do suggest that fast-paced reading may potentially lead to improved comprehension. These findings have implications for the type of language instruction used in classrooms and, therefore, for teachers of adult ESL learners.